2017
DOI: 10.1016/j.cedpsych.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and coping with the stress of assessment: Gender differences in outcomes for university students

Abstract: The main objectives of the present research were to test a conceptual model linking motivational processes involved in coping with the stress of university assessment, and to examine gender differences in these processes. Self-determined motivation was hypothesized to predict coping strategies and the response to assessment-related stress, and coping was hypothesized to play a considerable role in short-and long-term outcomes of assessment. We examined this model using multiple group path analysis in Mplus. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
93
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 94 publications
13
93
1
4
Order By: Relevance
“…This may imply that Saudi Arabia, having a patriarchal family structure, imposes more stress on their female kin especially those involved in academe. This is concurred by Bonneville-Roussy, where women in universities experienced higher levels of stress and mostly affected by disengagement-oriented coping [37].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This may imply that Saudi Arabia, having a patriarchal family structure, imposes more stress on their female kin especially those involved in academe. This is concurred by Bonneville-Roussy, where women in universities experienced higher levels of stress and mostly affected by disengagement-oriented coping [37].…”
Section: Discussionsupporting
confidence: 63%
“…However, different studies, where the PSS-10 was used, obtained a reliability test of >.70 [22][23][24][25]. Level of stress was classified as: low stress (0-13); moderate stress (14-26); high stress (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Methodsmentioning
confidence: 99%
“…Relations between educational stress experienced during the learning process and various factors have been the subjects of several studies. Its relations with such factors as success, learning strategies (Laakkonen and Nevgi, 2014) and gender (Bonneville-Roussy et al, 2017) were dealt with in the literature. Yıldırım et al (2017) examined the relations between educational stress and ways of coping with stress and self-respect, social support and general health status in 517 nursing students and found that educational stress and ways of coping with stress are significantly related to self-respect and social support and are affected by general health status.…”
Section: Relationships Between Educational Stress and Attitudes To Lementioning
confidence: 99%
“…5,24,[46][47][48][49][50] Kaya et al 45 reported that male students use active coping more than female students while Savcı and Aysan 29 reported that perceived stress is higher in female students than in male students, which might be due to the differences in the way men and women are raised and societal roles they are expected to play. 51 Most participants with negative income and a bad relationship with their family use effective coping styles less often than others.…”
Section: Coping Styles According To Personal Characteristicsmentioning
confidence: 99%